Public value creation dalam Transformasi Digital Pemerintahan: Suatu Tinjauan Literatur - Teraya Dewiayus Khasturi; Atikah .; Naina Affendy; Boni Saputra; M. Fachri Adnan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Government digital transformation has become a global strategic agenda that fundamentally reshapes the public service paradigm. However, a critical question remains inadequately addressed: to what extent does digital transformation genuinely create public value for citizens? This article aims to analyze the concept of public value creation within the context of government digital transformation through a literature review of twenty scientific articles published between 2022 and 2026. The findings indicate that government digital transformation holds significant potential for creating public value through enhanced service efficiency, transparency, accountability, and citizen participation. Mark Moore’s Strategic Triangle theory serves as the dominant analytical framework linking digital innovation to public value creation. Nevertheless, the digital divide, low digital capacity among government officials, and data system fragmentation remain major barriers limiting inclusive public value realization. This study recommends digital-based co-production approaches, strengthening digital literacy for citizens and officials, and integrating national service platforms (INA Digital, SPBE) as instruments for sustainable public value creation.